VIBRATION AND BONE - AN OPTION FOR LONG-TERM SPACE MISSIONS? - Jörn Rittweger (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2012)
Bone is lost during sojourns in microgravity. Thus to prevent fractures in future manned inter-planetary missions, efforts are currently being made to develop effective countermeasures. Bones adapt to mechanical stimuli, and biomechanical analysis suggests that muscle forces play an important role. Thus, resistance training is advocated as first option for a countermeasure modality. In addition, vibration has certain characteristics (well controllable, rapid stretch-shortening and large rate of contractions) that could be of interest. Studies of the past decade have shown that conventional resistive exercise may be sufficient to maintain bone when performed on a daily basis, but when performed only every other day. Whole body vibration without additional load seems to be in-effective, but it shows good potential, and probably a genuine effect upon bone when combined with additional loads in the order of twice the body weight. Thus, there is now accumulating evidence to suggest that effective exercises exist to counteract microgravity-related bone loss. At least for bed rest, forceful muscle contractions seem to be a prerequisite. They may be fortified, but probably not replaced, by vibration exposure.